Website Based Information System for Sales and Purchasing of Traditional Fish for Kalanganyar Residents - Ahmad Rizqi Efendi; Yulian Findawati (Procedia of Engineering and Life Science, 2021)
The purpose of this research is to create an information system that can be used for buying and selling websites. The research method used is the waterfall method, but the data collection techniques used are observation, interviews, and literature study. Where to get the data, it is necessary to come directly to the location which is the place of research. Later, the result of this research is that circles of people can sell products online and can expand the reach of website based marketing, buyers only need to access the website to make purchase transactions